Web-based ionic liquids learning media to measure the competence of the Polytechnic student - Ina Yulianti; Ida Hamidah; Mumu Komaro; Ahmad Mudzakir; Maizam Alias (OmniaScience, 2021)
The rapid development of technology and information has influenced students' learning styles and has led to a shift in information seeking from paper books to e-books. The purpose of this study is to measure the competence of students on the ionic liquid material, including ionic liquid knowledge, attitude, and skills, as well as website knowledge. The research sample is Chemical Engineering students in a private polytechnic in Indonesia and taken through a purposive sampling technique. This website-based learning is tested on students through the experiential learning model. Data collection was carried out by filling out a Likert scale competency test at the beginning and the end of the study. The results revealed that website-based ionic liquid learning attracted the attention of students, but not all students can do it independently yet. The learning still has to be combined with lecturers' explanations as reinforcing concepts. The implications of this research are expected to be used as recommendations in enriching the Chemical Engineering education curriculum by adding website-based ionic liquid material.